O pneumoperitônio aquecido e umidificado altera a superfície morfológica peritoneal e os marcadores de estresse oxidativo em gatas? - Engelsdorff, João Segura (2024)
To perform videolaparoscopy procedures, it is necessary to distend the abdominal cavity to create a safe and efficient working space for carrying out minimally invasive procedures. The most common way to create a workspace is to establish pneumoperitoneum with carbon dioxide. The present study aimed to evaluate the influence of standard pneumoperitoneum in comparison to heated and humidified pneumoperitoneum in felines females undergoing laparoscopic ovariectomy and its influence on body temperature, biomarkers of oxidative stress and peritoneal histology. The present study included 16 cats that were distributed into two groups one being a heated and humidified group, this group used carbon dioxide (CO2) previously heated and humidified to establish pneumoperitoneum and the other standard group, that used CO2 cold and dry. The evaluation of oxidative stress and peritoneal histology were collected at T0 this being the exact moment that pneumoperitoneum of 8mmHg and T1 at 50 minutes of pneumoperitoneum were establish. Body temperature was measured after orotracheal intubation (T0) and every 5 min using the esophageal thermometer on the surgical monitor from T5 to T70. The oxidative stress biomarkers evaluated were Catalase (CAT), thiobarbituric acid reactive substances (TBARS) and glutathione transferase (GSTs). Body temperature does not have significant difference between the GAU and GP at any of the times present. There was also no significant difference between the GAU (-3,09±0,65) and GP (-2,88±0,37) in temperature variation during the first 70 minutes of surgery (p=0,467). The Kruskal-Wallis non-parametric test demonstrated a significant reduction in CAT activity values in GP in relation the GAU whiting 50 minutes (p=0,0096). The t-student has no significance difference in the TBARS between GAU (0,79±7,07) an GP (-0,59±4,17) (p= 0,067), as well as in evaluation of the ANOVA variation test do TBARS variation (p=0,63). GPx activity showed no significant difference in the treatment variable (GAU x GP) p= 0.50. We can conclude that the heating and humidification of the CO2 used to obtain pneumoperitoneum generated lower consumption of the CAT enzyme in the feline species in relation to standard CO2.